CSR (Corporate Social Responsibility) Of PT. Sarihusada And Community Empowerment-Based Integrated Service Post (Posyandu) to Establish A Child Friendly Village In Yogyakarta Indonesia - Agustinawati, Eva Agustinawati; Karsidi, Ravik; Tri Kartono, Drajat; Kusnandar, Kusnandar (Advances in Social Sciences Research Journal, 2020)
Badran in Yogyakarta which is located in the river bank of Winongo river used to be known as a dirty and slum area. Some children were malnourished due to unhealthy food and environment. This situation led people to being determined to establish a village that is more conducive for children. In cooperation with PT. Sarihusada, the community empowered Posyandu(Integrated Service Posts) to help them improve their health especially toddlers. This research is a qualitative research since the research findings based on the research problems, purposes, approaches as well as analysis cannot be achieved by using statistical or quantitative approaches.This reasearch uses primary and secondary data sources. The sampling techniques used in this research are purposive sampling and snowball sampling. The data collecting technique was conducted through interactive methods including in-depth interviews, participant observation, and Focus Group Discussion (FGD).The data validation in this research was conducted by using the source triangulation and data analysis which consists of data reduction, data display and conclusions. The results of the research demonstrate that the Integrated Service Posts (Posyandu) that exist in Badran village are the results of collaboration between the people of the village and the CSR of PT. Sarihusada through Rumah Srikandi (The House of Srikandi). The operation of the Posyandu is managed fully by the cadres of the Posyandu itself who come from the Badran village. The nutritionists of PT. Sarihusada mentored the mothers who have toddlers the ways to process healthy and nutritious food. Furthermore, PT. Sarihusada also provides milk for toddlers everytime the service held at Posyandu. After the CSR program of PT. Sarihusada has been completed, people contributed 500 rupiahs a month for the operational costs of the Posyandu sustenance.